Crucial Roles of miR-625 in Human Cancer - Zhang, Menggang; Xiong, Fei; Zhang, Shuijun; Guo, Wenzhi; He, Yuting (Frontiers in Medicine, 2022)
Genetic and epigenetic characteristics are core factors of cancer. MicroRNAs are small non-coding RNAs (ncRNAs) which regulate gene expression at the post-transcriptional level via binding to corresponding mRNAs. Recently, increasing evidence has proven that miRNAs regulate the occurrence and development of human cancer. Here, we mainly review the abnormal expression of miR-625 in a variety of cancers. In summarizing the role and potential molecular mechanisms of miR-625 in various tumors in detail, we reveal that miR-625 is involved in a variety of biological processes, such as cell proliferation, invasion, migration, apoptosis, cell cycle regulation, and drug resistance. In addition, we discuss the lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA networks and briefly explain the specific mechanisms of competing endogenous RNAs. In conclusion, we have revealed the potential value of miR-625 in cancer diagnosis, treatment, and prognosis and hope to provide new ideas for the clinical application of miR-625.